ANALYSIS OF RELATIONSHIP GESTATIONAL DIABETES MELLITUS WITH NEWBORN BABY WEIGHT AND LENGTH - Enda Silvia Putri; Marniati; Khairunnas; Sufyan Anwar; Itza Mulyani; Siti Maisyarah Fitri Siregar; Sukma Elida; Suci Eka Putri; Ernawati; Arfriani Maifizar (RADJA PUBLIKA, 2024)
Gestational Diabetes Mellitus (GDM), was a condition in which pregnant women experience higher blood sugar levels than usual. This can affect the development of the fetus and the health of the newborn. The purpose of the reasearch was to analyze the gestational relationship of diabetes mellitus with the newborn's weight and height. The research method uses a quantitative method with cross sectional design, the sample represents a total population of 126 people, data analysis using a chi square test using the application of SPSS 21.0. The results of the study show that there was a relationship between GDM and weight with values (P Value =1,00 ≥ α :0,05 and RP = 1,00) and the length of the newborn with value (P value =0,695 ≥ alpha :0,05, RP = 2,00). An abnormal blood sugar level in the mother during pregnancy affects the nutrition received by the fetus so affecting the length of the baby. Important advice for mothers at the time of pregnancies to observe blood sugar levels at normal levels by paying attention to nutrition intake and stress management through regular consultation with the nearest health officials and health services on a regular basis during the pregnant, so that the baby is born healthy especially the length of the body.